2020
DOI: 10.1101/2020.09.17.302794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Evolution ofPseudomonas putidaunder Silver Ion versus Nanoparticle Stress

Abstract: SummaryWhether the antibacterial properties of silver nanoparticles (AgNPs) are simply due to the release of silver ions (Ag+) or, additionally, nanoparticle-specific effects, has been debated for over a decade. We used experimental evolution of the model environmental bacterium Pseudomonas putida to ask whether bacteria respond differently to Ag+ or AgNP treatment. We pre-evolved five cultures of strain KT2440 for 70 d without Ag to reduce confounding adaptations before dividing the fittest pre-evolved cultur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Although a growing body of research has shown that bacteria can readily evolve resistance towards metallic NPs [13,15,95], the genetic basis of NP resistance remains poorly understood. Recent studies reported that NP resistance might evolve through few mutations or without any significant genetic changes in different bacterial species.…”
Section: Strategies To Overcome Bacterial Resistance Towards Metallicmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a growing body of research has shown that bacteria can readily evolve resistance towards metallic NPs [13,15,95], the genetic basis of NP resistance remains poorly understood. Recent studies reported that NP resistance might evolve through few mutations or without any significant genetic changes in different bacterial species.…”
Section: Strategies To Overcome Bacterial Resistance Towards Metallicmentioning
confidence: 99%
“…Graves and collaborators detected few genetic changes in AgNP-resistant isolates of E. coli K-12 obtained in laboratory evolution experiments, although the contribution of these mutations to NP resistance has not been investigated yet [15]. In addition, Dong and coworkers reported that mutations in AgNP-resistant populations were mainly associated with the cell surface and two component systems [95]. Recently, Panacek and collaborators showed that three strains of E. coli and P. aeruginosa evolved Ag-NP resistance by overproducing flagellin, the main flagella protein, to facilitate NP aggregation and immobilization outside cells [13].…”
Section: Strategies To Overcome Bacterial Resistance Towards Metallicmentioning
confidence: 99%